SOUTH CHINA SEA DISPUTE - Muhammad Rizky Prawira (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2018)
During the past decade, China has been striving for a more prominent status in the international community. In doing so, China undertook several measures that indicate its willingness to become a supportive collaborator in the international politics, including taking a part in the Six Party Talks regarding to the North Korean nuclear issue as well as striving for the Market Economy Status (MES). However, the recent development of the South China Sea dispute seems to show a contrasting circumstance. As one of the claimant states, China showed a fairly aggressive gesture in expanding and exploiting the disputed territory. Recently, China even declared a refusal against the verdict from the international law which stated that China had no legal base in claiming the territory. This situation sparked a puzzle as the non-compliance against the international law seemed to be violating China’s on- going efforts to win the broader acceptance in the international community. Thus, using two different perspectives, namely structural realism and social constructivism, this study analyses puzzle and finds the contextual relevance behind China’s non- compliance policy. The overall findings show that the rational interest of pursuing the hegemony in the disputed region becomes the primary goal that China is pursuing beyond the interest of adhering to the international law.